A survey of the needs and utilization of health information among young adults in Ogun state, Nigeria (2015)
"Good health is an indispensable prerequisite for the socio-economic development of any country. The increasing number of health related problems among young adults in Nigeria warrants urgent and special attention. This study, therefore focused on health information needs and utilisation among young adults. Correlational research design was adopted for this study using descriptive survey method. Questionnaires were designed and used as survey instruments. The target population for this study were young undergraduates within the ages of 16-24 years. Federal University of Agriculture and Crescent University were selected because they are the two universities within the city of Abeokuta. The study used 25% of undergraduate students from each of the 35 departments that made up 8 colleges in the two universities for the study. Hence, the sample size for this study was 1,745 young adults. A total number of 1,745 copies of questionnaire were administered to the respondents. This study finds that nutrition ranked highest, followed by water treatment, sanitation and diagnosed medical condition among the health information needs of the young adults. Young adults also need health information to avoid unwanted pregnancy, unsafe abortion and HIV/AIDS infection. Access to health information was mostly through textbooks and newspapers/magazines. In addition, the study finds that they also had access to electronic media like radio, television, Internet and GSM mobile phones. This study finds that religious beliefs against the use of drugs ranked highest among the problems that hinder effective health information utilisation among young adults in Nigeria. Conclusion was drawn based on the findings and recommendations were proffered."